Estudo do comportamento de concretos asfálticos com diferentes tipos de agregados e cales - Boeira, Fernando Dekeper (2014)
Pavements are highly relevant structures in the current economic context and its performance depends, among other factors, on the component of the materials of each layer of the structure. One of the solutions studied is the addition of lime to the asphalt concrete (AC), which improves the adhesion between the asphalt binder and the aggregates and also changes the mechanical properties of the blends. The DNIT (National Department of Transport Infrastructure) has specified, since 2009, the addition of lime to AC mixtures on Brazilian federal highways, however does not specify the mineral composition of the limes neither determines the types of aggregates to add to the mixture. The scope of this study is to evaluate the effects of the addition of different types of limes and different types of aggregates to AC mixtures, as well as the mechanical properties and the adhesion of the mixture. Two types of limes were used in this study, a dolomitic lime produced in the state of Rio Grande do Sul and a calcite lime from the state of Minas Gerais, both added in the content of 1.5% of the dry coarse aggregate. The sources of the six different aggregates used in this study were chosen to cover the main geological formations in the state of Rio Grande do Sul. Besides, it was used as comparison data collected from previous researches (Boeira, 2011). The mixtures were design by the Marshall methodology, and three different AC mixtures were designed using each aggregate: Reference; 1,5% calcite and 1,5% dolomite. Experiments were made to analyze the mechanical behavior (test Tensile Strength by Diametral Compression and Resilience test Module) and check the properties of adhesion (Modified Lottman Methodology), Wear (Cantabro test) and the test Adhesion Ligand Bituminous (were performed Coarse aggregate). From the research it is possible to formulate the AC with high modulus of resilience and tensile strength, and also control the deleterious effects of water by the addition of hydrated lime. The behavior of the mixtures will depend on the geological formations of each aggregate used, depending on the mineral composition the effect can be minimal or critical for the success of the mixture. It appears that the aggregate of Eldorado do Sul, Caçapava do Sul and Bagé were the ones with improvements regarding the addition of limes.